Time-restricted feeding attenuated hypertension-induced cardiac remodeling by modulating autophagy levels in spontaneously hypertensive rats - Yi, Xin; Abas, Razif; Raja Muhammad Rooshdi, Raja Abdul Wafy; Yan, Jie; Liu, Canzhang; An, Jiaxu; Daut, Ummi Nadira (Nature Research, 2025)
To investigate whether time-restricted feeding (TRF) can alleviate cardiac remodeling in spontaneously hypertensive rats (SHRs) by regulating autophagy levels. A 16-week TRF intervention was conducted on Wistar Kyoto (WKY) rats and SHRs, with dietary intake confined to the interval from 9:00 am to 5:00 pm each day. The study examined the impact of TRF on blood pressure (BP), cardiac morphology and function, and the expression levels of key proteins involved in autophagy and its associated signaling cascades. Transmission Electron Microscopy (TEM) was utilized to further evaluate autophagic changes in left ventricular (LV) tissues. TRF significantly mitigated systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean blood pressure (MBP) in SHRs. Additionally, TRF improved ejection fraction (EF) and diminished interventricular septal thickness at end-diastole (IVS-d). The study further revealed that TRF enhanced the expression of microtubule-associated protein-I light chain 3 (LC3-I), while reducing that of microtubule-associated protein-II light chain 3 (LC3-II). Moreover, TRF suppressed the expression levels of Beclin-1, phosphorylated phosphoinositide 3-kinase (p-PI3K), phosphorylated protein kinase B (p-AKT), and phosphorylated mechanistic target of rapamycin (p-mTOR) in the LV tissues. TEM analysis confirmed that TRF could inhibit autophagy levels in the LV tissues. TRF can attenuate cardiac remodeling in SHRs by regulating autophagy levels.